2019
DOI: 10.4012/dmj.2018-064
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of a glass ionomer cement incorporated with Amazon plant extract

Abstract: To evaluate the mechanical properties (MP) and antimicrobial activity of a glass ionomer cement (GIC) incorporated with an antimicrobial agent from the aerial parts of Dioscorea altissima. MP were: syneresis & imbibition; solubility; elasticity module; surface microhardness and fluoride release, and the anti-Streptococcus mutans (Smut) activity was accessed by microdilution broth assay and 3-(4,5-Dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) analysis. Syneresis & imbibition did not change ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Green chemistry route is followed in the synthesis of polyalkenoic acid since its Review Materials Advances invention. Recent studies showed that researchers around the globe have claimed green synthesis routes for GIC using different additives such as carbohydrates, 70,71 organic acids [72][73][74] and other plant-based [75][76][77] materials to enhance its properties. For example, Dola Sundeep et al investigated the effect of silver nanoparticles synthesized from the Mangifera indica leaves and studied the antimicrobial effect against Escherichia coli and Staphylococcus aureus at different concentrations in GIC.…”
Section: Green Chemistry Route For the Synthesis Of Polyalkenoic Acidmentioning
confidence: 99%
“…Green chemistry route is followed in the synthesis of polyalkenoic acid since its Review Materials Advances invention. Recent studies showed that researchers around the globe have claimed green synthesis routes for GIC using different additives such as carbohydrates, 70,71 organic acids [72][73][74] and other plant-based [75][76][77] materials to enhance its properties. For example, Dola Sundeep et al investigated the effect of silver nanoparticles synthesized from the Mangifera indica leaves and studied the antimicrobial effect against Escherichia coli and Staphylococcus aureus at different concentrations in GIC.…”
Section: Green Chemistry Route For the Synthesis Of Polyalkenoic Acidmentioning
confidence: 99%